Community Resistance to Femicide in West Java: Social Responses, Peace Actions, and Opposition to Violence against Women - Mochamad Ziaul Haq; Gerardette Philips; Stephanus Djunatan; Henrycus Napitsunargo; F.X. Galih Kurniawan; Renatha Aisya Nazwanindya (Khazanah Sosial, 2025)
This study analyzes how civil society communities in Indonesia—particularly in West Java and Yogyakarta—respond to and resist femicide as the most extreme form of gender-based violence. The research is driven by the growing prevalence of femicide and the absence of legal recognition of its structural and gendered nature in Indonesia. Employing a qualitative approach and a collective case study design, this study focuses on six grassroots organizations: Sekolah Damai Indonesia Bandung, Perspektif Sosiologi, Iteung Gugat, Youth, Interfaith and Peace (YIP) Center, Puan Hayati, and Srikandi Lintas Iman. Data were gathered through interviews, participatory observation, and document analysis. The findings reveal that these communities play critical roles not only in advocacy but also in psychosocial support, safe space formation, and the production of counter-narratives that confront patriarchal and symbolic violence. Functioning as cultural, political, and therapeutic agents, they fill the gaps left by institutional inaction. However, the study also highlights structural dysfunction: the burden of advocacy is disproportionately placed on these communities, while systemic failures in law, media, and education continue to normalize gender-based violence. Theoretically, the study integrates Berger and Luckmann’s theory of social construction with Galtung’s concept of structural violence and positive peace to frame femicide as both symbolic and systemic. This research contributes original insights to Indonesian gender studies by mapping community-based resistance to femicide—an area rarely examined—and by emphasizing the urgency of intersectoral policy reform and institutional support.